Green Synthesis of Carbon Nanotubes from Coconut Shell Waste for the Adsorption of Pb(II) Ions - Yusuf Zaim Hakim; Yoki Yulizar; Adi Nurcahyo; Magun Surya (Chemistry Education Program, the University of Mataram, 2018)
Numerous complex methods have been developed for the preparation of carbon nanotubes (CNT) such as laser vaporization, arc discharge, pyrolysis, and chemical vapour deposition (CVD). In this study, an environmentally friendly and convenient method called one-step water assisted (quenching) synthesis method was conducted from graphite flakes, which were taken from coconut shell wastes to produce carbon nanotubes. Chemical and physical structure of the carbon nanotubes were characterized by FTIR (Fourier Transform Infrared), Scanning Electron Microscope (SEM), and Transmission Electron Microscopy (TEM). Adsorption performance of heavy metals Pb(II) ions by CNTs has been evaluated using the stirring method, and the concentration of Pb(II) ions has been determined using Atomic Absorption Spectroscopy (AAS). The adsorption conditions such as pH and contact time have been obtained. The results showed that carbon nanotubes were a bit successfully formed, in which the tubes distribution are scattered irregularly. The average tube diameter was 123 nm. During the adsorption test, it was found that the adsorption was proportional to the contact time, in which the optimum contact time was 20 minutes. The optimum pH of Pb(II) ions absorption was 5 where the potential for Pb(II) ions absorption was 120 %. The results indicate the true potential of this green chemistry based method, and it opens the chance for possibility to produce carbon nanotubes at a larger scale.